Dampak Media Sosial Tiktok Terhadap Tindak Tutur Siswa Sekolah Dasar - Elsa Totti Bakistuta; Muhammad Abduh (Elementary Teacher Education Program, Majalengka University, 2023)
Social media is a technology that is often used by people for communication. One of the social media that is often accessed is Tiktok. Tiktok features many interesting features, one of which provides free information and can be accessed anywhere and anywhere. Many Tiktok users are young and old, even elementary school students. This study aims to explore the impact of Tiktok social media on student speech acts and reveal teachers' efforts to overcome the impact of Tiktok. Analytical qualitative descriptive technique is this research method and the data source comes from several teachers and grade VI students of SD Muhammadiyah Plus Malangjiwan. Observation, interviews and questionnaires are data collection techniques. Miles & Huberman's interactive data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions from research. The results and discussions of Tiktok social media students and teachers see more interesting content such as mukbang, freefire, a day in my life, and so on. The use of Tiktok has a positive impact on speech acts, one of which is students proficient in English and Arabic. The negative impact of Tiktok is that students often talk dirty because they often see content that uses bad words.